Pulmonary endarterectomy in the octogenarian population: safety and outcomes. Issue 7 (July 2021) - Grazioli, Valentina; Ghio, Stefano; Pin, Maurizio; Sciortino, Antonio; Celentano, Anna; Silvaggio, Giuseppe; Monterosso, Cristian; Turco, Annalisa; Klersy, Catherine; Merli, Vera N.; Vanini, Benedetta; D'Armini, Andrea M.
Abstract : Aims: Aim of the study was to verify the feasibility, safety and efficacy of pulmonary endarterectomy (PEA) in octogenarian patients with chronic thromboembolic pulmonary hypertension. Methods: We retrospectively analyzed 635 chronic thromboembolic pulmonary hypertension patients who underwent PEA at our center and were followed-up for at least 1 year. The end-points of the study were in-hospital mortality, hemodynamic results at 1 year and long-term survival. Results: In-hospital mortality was 4, 10 and 17%, respectively, for 259 patients under the age of 60 years, 352 aged between 60 and 79 years and 24 octogenarians ( P  = 0.006 octogenarians vs. <60 years). At multivariable analysis, age and pulmonary vascular resistances were independent risk factors for mortality ( P  = 0.021 and P  < 0.001, respectively). At 1 year, the improvement in cardiac index was lower and the distance walked in 6 min was poorer for octogenarians than for the other two groups (both P  = 0.001). Survival after hospital discharge was similar over a median follow-up period of 59 months ( P  = 0.113). Although in-hospital mortality and long-term survival are similar in octogenarians as compared with patients aged between 60 and 79, the improvement in cardiac index and in functional capacity at 1 year are lower in this very elderly population. Conclusion: Age over 80 years should not be a contraindication to PEA surgery in selected patients operated on in referral centers. Abstract : Supplemental Digital Content is available in the text